The pursuit of happiness : how classical writers on virtue inspired the lives of the founders and defined America - Rosen, Jeffrey, 1964- (Simon & Schuster, 2024)
"The Declaration of Independence identified 'the pursuit of happiness' as one of our unalienable rights, along with life and liberty. Jeffrey Rosen profiles six of the most influential founders--Benjamin Franklin, George Washington, John Adams, Thomas Jefferson, James Madison, and Alexander Hamilton--to show what pursuing happiness meant in their lives. By reading the classical Greek and Roman moral philosophers who inspired the Founders, Rosen shows us how they understood the pursuit of happiness as a quest for being good, not feeling good--the pursuit of lifelong virtue, not short-term pleasure. Among those virtues were the habits of industry, temperance, moderation, and sincerity, which the Founders viewed as part of a daily struggle for self-improvement, character development, and calm self-mastery. They believed that political self-government required personal self-government. For all six Founders, the pursuit of virtue was incompatible with enslavement of African Americans, although the Virginians betrayed their own principles"--